NARASI PERCINTAAN DAN KESETARAAN GENDER DALAM LIRIK LAGU-LAGU TULUS - Tania Intan (Kafa`ah: Journal of Gender Studies, 2020)
Besides rhythm, song lyrics are an important part of a song. As a medium for the expression of the author, song lyrics can be a means of socialization and preservation of certain values, so that they are often regarded as literary works as well as poetry. Song lyrics were written and sung by Tulus for example, are considered to contain their perspectives on love relations and gender equality. The songs Teman Hidup, Sepatu, Jangan Cintai Aku Apa Adanya, and Tuan Nona Kesepian are the objects of this study which was studied with descriptive-qualitative analysis methods, through the approach of feminist studies and popular culture. The results showed that in these songs, it was revealed that women tend to be positioned parallel to men. Like men, women are seen to be able to make decisions, are brave, and strong in solving problems. Research on gender equality [or inequality] in various popular culture media such as songs does need to be carried out continuously to build insight and awareness of the audience.